The role of the NOTCH1 signaling pathway in the maintenance of mesenchymal stem cell stemness and chondrocyte differentiation and its potential in the treatment of osteoarthritis - Fuming Wu; Haiquan Yu (Journal of Orthopaedic Surgery and Research)
Abstract Objective This study aims to explore the potential role of mesenchymal stem cells (MSCs) in the treatment of osteoarthritis (OA), particularly the function of the NOTCH1 signaling pathway in maintaining the stemness of MSCs and in chondrocyte differentiation. Methods Utilizing diverse analytical techniques on an osteoarthritis dataset, we unveil distinct gene expression patterns and regulatory relationships, shedding light on potential mechanisms underlying the disease. Techniques used include the culture of MSCs, induction of differentiation into chondrocytes, establishment of stable cell lines, Western Blot, and immunofluorescence. Through the construction of lentiviruses overexpressing and knocking out NOTCH1, the effects of NOTCH1 on the stemness of MSCs and chondrocyte differentiation were investigated. Additionally, the effects of NOTCH1 on chondrocyte homeostasis and apoptosis were evaluated by adding the EZH2 inhibitor GSK126 and the endoplasmic reticulum stress inducer tunicamycin. Results Experimental results demonstrated that NOTCH1 expression can influence the maintenance of MSC stemness and chondrocyte differentiation by regulating EZH2. Knockout of NOTCH1 decreased the expression of chondrocyte markers, while overexpression increased their expression. Under conditions of endoplasmic reticulum stress, NOTCH1 expression helped reduce the expression of stress-related proteins, maintain chondrocyte homeostasis, and inhibit apoptosis. Conclusion The NOTCH1 signaling pathway plays a crucial role in maintaining the stemness of MSCs, differentiating into chondrocytes, and in the treatment of osteoarthritis. NOTCH1 influences the differentiation fate of MSCs and the homeostasis of chondrocytes by regulating EZH2 and other related genes, offering new targets and strategies for the treatment of diseases like osteoarthritis.